POTENTIAL IMMUNOMODULATION ACTION OF PARTIAL ACYLATED INTERLEUKIN-2 IN EXPERIMENTS - Romanova, E.A.; Martynov, A.V.; Igumnova, N.I.; Sidorenko, T.A.; Chernyavsky, V.I.; Smelyanskaya, M.V.; Peremot, S.D. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
In the article were presented results about studied of immunopotential activity of new IL-2 – acylated derivatives. It was show, that preparation much increased spontaneous blasttransformation of lymphocytes in mice as in vitro and in vivo. Added of acIL-2 to lymphhocete’s cells culture resulted to more increasing of mitotic activity of lymphocytes than in control with native Roncoleukin.